Meta-analysis of the use of sterilized mosquito net mesh for inguinal hernia repair in less economically developed countries. Issue 4 (27th February 2019) - Ahmad, M H; Pathak, S; Clement, K D; Aly, E H
Abstract: Background: Inguinal hernias are common in less economically developed countries (LEDCs), and associated with significant morbidity and mortality. Tension-free mesh repair is the standard treatment worldwide. Lack of resources combined with the high cost of commercial synthetic mesh (CSM) have limited its use in LEDCs. Sterilized mosquito net mesh (MNM) has emerged as a low-cost, readily available alternative to CSM. The aim of this systematic review and meta-analysis was to evaluate the safety and efficacy of MNM for the use in hernia repair in LEDCs. Methods: A systematic review and data meta-analysis of all published articles from inception to August 2018 was performed. Cochrane Central Register of Controlled Trials, MEDLINE and Embase databases were searched. The primary outcome measure was the overall postoperative complication rate of hernia repair when using MNM. Secondary outcome measures were comparisons between MNM and CSM with regard to overall complication rate, wound infection, chronic pain and haematoma formation. Results: A total of nine studies were considered relevant (3 RCTs, 1 non-randomized trial and 5 prospective studies), providing a total cohort of 1085 patients using MNM. The overall complication rate for hernia repair using MNM was 9·3 per cent. There was no significant difference between MNM and CSM regarding the overall postoperative complication rate (odds ratio 0·99, 95 per cent c.i. 0·65 to 1·53; P = 0·98), severe or chronic pain (OR 2·52, 0·36 to 17·42; P = 0·35), infection (OR 0·56, 0·19 to 1·61; P = 0·28) or haematoma (OR 1·05, 0·62 to 1·78; P = 0·86). Conclusion: MNM has a low overall postoperative complication rate and is unlikely to be inferior to CSM in terms of safety and efficacy. MNM is a suitable low-cost alternative to CSM in the presence of financial constraint. Graphical Abstract: Sterilized mosquito net mesh (MNM) has emerged as a low-cost, readily available alternative to commercial synthetic mesh (CSM). This analysis suggests that MNM has an overall low postoperative complication rate and is unlikely to be inferior to CSM in terms of safety and efficacy. MNM is potentially a suitable alternative to CSM in the presence of financial constraints. Still not sure about long-term durability